Quantitative Proteomic Analysis of Mouse Sciatic Nerve Reveals Post-injury Upregulation of ADP-Dependent Glucokinase Promoting Macrophage Phagocytosis - Zhang, Kai; Wang, Qingyao; Liang, Yiyao; Yan, Yu; Wang, Haiqiong; Cao, Xu; Shan, Bing; Zhang, Yaoyang; Li, Ang; Fang, Yanshan (Frontiers in Molecular Neuroscience, 2021)
Nerve injury induces profound and complex changes at molecular and cellular levels, leading to axonal self-destruction as well as immune and inflammatory responses that may further promote neurodegeneration. To better understand how neural injury changes the proteome within the injured nerve, we set up a mouse model of sciatic nerve injury (SNI) and conducted an unbiased, quantitative proteomic study followed by biochemical assays to confirm some of the changed proteins. Among them, the protein levels of ADP-dependent glucokinase (ADPGK) were significantly increased in the injured sciatic nerve. Further examination indicated that ADPGK was specifically expressed and upregulated in macrophages but not neurons or Schwann cells upon injury. Furthermore, culturing immortalized bone marrow-derived macrophages (iBMDMs) in vitro with the conditioned media from transected axons of mouse dorsal root ganglion (DRG) neurons induced ADPGK upregulation in iBMDMs, suggesting that injured axons could promote ADPGK expression in macrophages non-cell autonomously. Finally, we showed that overexpression of ADPGK per se did not activate macrophages but promoted the phagocytotic activity of lipopolysaccharides (LPS)-treated macrophages. Together, this proteomic analysis reveals interesting changes of many proteins within the injured nerve and our data identify ADPGK as an important in vivo booster of injury-induced macrophage phagocytosis.